Pendampingan Aplikasi Alat Pelindung Diri pada Pemulung Sampah di Kelurahan Langkai Kota Palangka Raya - Fera Sartika; Suratno Suratno; Nurhalina Nurhalina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Waste pickers are the riskiest group for disease transmission through waste, so have Personal Protective Equipment (PPE) is needed as a tool used by workers to protect themselves against potential dangers and work accidents. Although there are no definitive data on the existence of accidents or occupational diseases in TPS or TPA, the risk of health problems or the spread of disease due to exposure to various types of waste is very possible. Likewise with the waste pickers who are in the Temporary Shelter (TPS) in the Kelurahan Langkai City of Palangka Raya. The purpose of community service activities is to assist in the application of PPE by providing education and socialization about the possibility of potential hazards and workplace accidents as garbage collectors and the risk of exposure to diseases that can be transmitted through waste, training, and demonstrations about the use of Personal Protective Equipment (PPE) when work and hand over a set of PPE tools to the scavengers. Community service activities carried out on 39 waste pickers in several TPS located in Kelurahan langkai city of Palangka Raya